PyTrA: ultra-fast transient absorption data analysis software. (21st April 2014) - Martin, Jacob; Wang, Xindi; Simpson, Cather; Siekmann, Ivo
Ultra-fast transient absorption spectra are inherently complex datasets to process. PyTrA is a new software system that has been written to bring together many of the most well-known techniques of analysis into one easy-to-use package. Figures of publishable quality can be generated, and advanced 3D graphs can be used to view the transient data in new ways. PyTrA is the first ultrafast transient analysis package that has Bayesian probabilistic fitting, implemented through the use of Markov chain Monte Carlo method in which the parameters can be randomly probed. This approach reduces the problems associated with over-describing the system.